KEANEKARAGAMAN JENIS BURUNG PADA AREAL TAMAN WISATA ALAM WERA, SIGI, SULAWESI TENGAH, INDONESIA - Evanjeli Evanjeli; Annawaty Annawaty; Ramadanil Ramadanil; Mohammad Ihsan (Biology Department, Mathematics and natural science, Tadulako University, 2019)
The objectives of this study were to determine the species composition, attendance level, species diversity and evenness of birds in Wera Nature Park, Sigi, Central Sulawesi. Data of birds was collected during February - March 2016 using point count method or IPA (Index Point of Abundance) by placing an observer at a systematically and predetermined point, then record and identify the birds directly by visually encountered or indirectly by voice. T-test was used to determine differences in bird species diversity between morning and afternoon at the 95% confidence level. During the study period, 35 avian species belonging to 21 families were identified. The families with most members were Colubridae and Cuculidae, each of the families have 6 species member. In addition, 6 endemic species to Sulawesi were also recorded. Based on the guild, 10 species of birds were 100% in the occurance. Results of evenness of birds and bird species diversity in Wera Nature Park did not differ significantly between morning and afternoon. It seems to be influenced by the availability of food in the Wera Nature Park both in the morning and afternoon. So TWA Wera is still a appropriate habitat for the bird life.